Pore development of the Lower Longmaxi shale in the southeastern Sichuan Basin and its adjacent areas: Insights from lithofacies identification and organic matter. (December 2020) - Zhang, Luchuan; Xiao, Dianshi; Lu, Shuangfang; Jiang, Shu; Chen, Lei; Guo, Tonglou; Wu, Liyuan
Abstract: X-ray diffraction (XRD), field emission/focusing ion beam scanning electron microscopy (FE-/FIB-SEM), nitrogen gas adsorption (N2 GA), and geochemical analyses were performed on the Lower Longmaxi shale in the southeastern Sichuan Basin and its adjacent areas to reveal the controls of shale lithofacies and organic matter (OM) on pore development. The results showed that the Lower Longmaxi shale primarily comprises three types of lithofacies based on shale compositions and sedimentary environment: OM-rich siliceous shale (ORSS), OM-moderate mixed shale (OMMS) and OM-lean argillaceous shale (OLAS). ORSS comprises high contents of OM and siliceous minerals (quartz and feldspar), deposited in a deep-water shelf and early semi-deep-water shelf environment, while OLAS consists of high clay mineral and low OM contents, primarily formed in a shallow-water shelf environment. OMMS witness a transition from ORSS to OLAS in sedimentary environment and shale components. OM hosts a higher volume of pores per unit weight compared to inorganic minerals, corresponding to 0.1878 ml/g and 0.00396 ml/g, respectively. OM-hosted pores are dominant in ORSS, constituting 72%, whereas OLAS mainly consists of mineral-hosted pores, comprising 63.2%. OM-hosted and mineral-hosted pores in OMMS exist in similar proportions, namely, 56.4% and 43.6%, respectively. Differentiated diagenetic paths resulting from sedimentary environment are responsible for the differences in pore development under various shale lithofacies. The thermal maturity, macerals, and abundance of OM all play a significant role in the morphology and development of OM-hosted pores. OM-hosted pores are primarily founded in migrated OM (mainly sapropelic type), instead of structured OM (mainly humic type), in the form of secondary pores that are derived from dry gas-generation stage. Furthermore, OM-hosted pore development in shale gas reservoirs is slowed or even reduced because of the weakening of shale's resistance to compaction resulting from excessively high OM content. Highlights: Division of ORSS, OMMS and OLAS based on shale components and sedimentary setting. A model to estimate pore volumes within OM and inorganic minerals is proposed. Lithofacies of various sedimentary settings show differences in pore development path. Maturity, abundance and maceral of OM control pore development in gas-mature shale.